CURRENT CAPABILITIES OF COMPUTED TOMOGRAPHY AND MAGNETIC RESONANCE IMAGING FOR THE DETECTION OF COMPLICATIONS AFTER COMBINED PANCREAS AND KIDNEY TRANSPLANTATION - R. Sh. Muslimov; F. A. Sharifullin; D. P. Katkov; A. V. Pinchuk; I. V. Dmitriev; R. V. Storozhev; B. D. Tugutov (Вестник рентгенологии и радиологии, 2017)
Objective: to give computed tomography (CT)- and magnetic resonance imaging (MRI)-based new anatomic-topographic relationships in patients after combined pancreas and kidney transplantation and to describe main visualization tasks and the types and frequency of various complications occurring in different periods after transplantation. Material and methods. Spiral CT and MRI images were analyzed in 45 patients after pancreas and kidney transplantation. A total of 51 studies (35 CTs and 16 MRIs) using intravenous contrast enhancement (n=34 (66%)) were performed. Results. A total of 55 complications, among which pancreatitis after pancreas transplantation was most common (55%), were found. Necrotizing pancreatitis following pancreas transplantation, which required open operative or percutaneous intervention, was diagnosed in 6.6%. Vascular complications were detected in 22%. Conclusion. The current capabilities of CT and MRI enable us to quickly obtain objective information on the status of transplanted organs, their vascular architectonics, as well as on the presence and type of occurred complications. Timely correction of identified complications positively affects the survival of transplanted organs and quality of life in a recipient.